Protein Arginine Methylation: An Emerging Modification in Cancer Immunity and Immunotherapy - Dai, Weijing; Zhang, Jianguo; Li, Siqi; He, Fajian; Liu, Qiao; Gong, Jun; Yang, Zetian; Gong, Yan; Tang, Fang; Wang, Zhihao; Xie, Conghua (Frontiers in Immunology, 2022)
Protein arginine methyltransferases (PRMTs) have emerged in recent years as a new member of the gene expression regulator family in eukaryotes and have been elucidated to be associated with cancer pathogenesis and progression. Cancer immunotherapy has brought significant improvements to cancer treatment in terms of overall survival and quality of life. Protein arginine methylation, as an epigenetic modification functions not only in transcription, RNA processing and signal transduction cascades, also plays an important role in almost all cancer-immunity cycle processes. Arginine methylation is involved in the activation of anti-cancer immunity and regulation of the efficacy of immunotherapy. In this review, we summarize the most up-to-date knowledge of the regulatory molecular mechanisms and various underlying signaling pathways of arginine methylation in cancer innate and adaptive immune responses, as well as the potential for PRMT-inhibitors to be an effective treatment in combination with immunotherapy.